TELAAH TENTANG TARI MINANGKABAU (The Study of Minangkabau Dance) - Efrida - (Institut Seni Indonesia Surakarta, 2006)
Minangkabau as an unity of tribe, geographical, and loaded culture with tradition values, istiadat adapt and fife of formed society and expand along with Minangkabau society growth alone. One of the uppermost matter at Minangkabau society [is] life [of] have their artistry [to], especially dance art. Divided Minangkabau society structure cause divided of embraced dance style become three, that is Target style, Surau style and Malay style. Third of style dance this embraced and developed by different faction so that cause difference also in the form of and its dance till. Nonetheless, that difference non meaning to indicate that dance style which is one more pre-eminent from other dance style. That difference show properties of multifarious creativity and tradition of faction inMinangkabau society in expressing artistic head in a life of have artistry to matching with life values which they embrace.